Diagnostics techniques in nonmuscle invasive bladder cancer - Ayman Soubra; Michael C Risk (Indian Journal of Urology, 2015)
Introduction: Nonmuscle invasive bladder cancer (NMIBC) is the most common presentation of bladder cancer and is often treatable with endoscopic resection and intravesical therapies. Cystoscopy and urine cytology are the gold standard in diagnosis and surveillance but are limited by their sensitivity in some situations. We seek to provide an overview of recent additions to the diagnostic armamentarium for urologists treating this disease. Methods: Articles were identified through a literature review of articles obtained through PubMed searches including the terms “bladder cancer”and various diagnostic techniques described in the article. Results: A variety of urinary biomarkers are available to assist the diagnosis and management of patients with NMIBC. Many have improved sensitivity over urine cytology, but less specificity. There are certain situations in which this has proved valuable, but as yet these are not part of the standard guidelines for NMIBC. Fluorescence cystoscopy has level 1 evidence demonstrating increased rates of tumor detection and prolonged recurrence-free survival when utilized for transurethral resection. Other technologies seeking to enhance cystoscopy, such as narrow band imaging, confocal laser endomicroscopy, and optical coherence tomography are still under evaluation. Conclusions: A variety of urine biomarker and adjunctive endoscopic technologies have been developed to assist the management of NMIBC. While some, such as fluorescence cystoscopy, have demonstrated a definite benefit in this disease, others are still finding their place in the diagnosis and treatment of this disease. Future studies should shed light on how these can be incorporated to improve outcomes in NMIBC.